Compatibility between Leptolegnia chapmanii and diflubenzuron and neem oil for the control of Aedes aegypti - Rueda Páramo, Manuel Enrique (2020)
Leptolegnia chapmanii is pathogenic to mosquito larvae. The compatibility between L. chapmanii and two insect growth regulators (IGR), diflubenzuron and neem oil, was evaluated. L. chapmanii was grown on culture media containing different concentrations of each IGR. The mycelial growth was significantly reduced with the highest concentrations of IGR (F₆,₉₈ = 268, p < 0.05). However, the production of zoospores (F₆,₅₆ = 0.93, p > 0.05) and the larval mortality of Aedes aegypti (F₆,₅₆ = 0.95, p > 0.05) were not significantly different among treatments. Furthermore, the percentage of adult emergence in the presence of different concentrations of diflubenzuron or a neem formulation was determined, and the pathogenic activity of zoospores was evaluated at the concentrations that inhibit the emergence at 30, 50 and 90%. The pathogenicity of zoospores was not significantly different among treatments (F₆,₁₄ = 0.54, p > 0.05), and the larval mortalities were above 90% in all cases.